Obesity, Body Fat Distribution, and Circulating Glutamate Concentrations, A BI-Directional Mendelian Randomization Study - Maltais-Payette, Ina (J Endocr Soc, 2021)
Background: Various observational studies have reported that circulating levels of the amino acid glutamate was significantly associated with central fat accumulation in men and women. This is the case in the Framingham Heart Study Generation 3 for waist circumference, in the TwinsUK cohort for trunk fat and in a cohort of 1449 Japanese for visceral adipose tissue area measured by computed tomography. However, whether the association between abdominal adiposity and circulating glutamate is causal, as well as the direction of this association, is unknown. Here, we aimed to determine whether obesity and abdominal obesity were causally associated with circulating glutamate levels. Methods: We used a two-sample bi-directional inverse-variance weighted Mendelian randomization study design (IVW-MR). We derived summary statistics for our exposures and outcomes from published genome-wide association studies from the GIANT consortium (n = 681 275) and blood metabolites (n = 7 804). We identified independent genetic variants (r(2) < 0.1) associated with body mass index (BMI) and waist-to-hip ratio adjusted for BMI (WHRadjBMI, p < 5x10(-8)) as well as circulating glutamate (p < 5x10(-5)). Results: We found no causal association between circulating glutamate levels and BMI (beta = 0.082, SE = 0.0413, p = 0.0471) or WHRadjBMI (beta = -0.00106, SE = 0.0401, p = 0.979). However, there was a positive effect of BMI (beta = 0.0608, SE = 0.0150, p = 5.19x10(-5)) and WHRadjBMI (beta = 0.0701, SE = 0.0198, p = 3.98x10(-4)) on circulating glutamate level. Conclusion: This Mendelian randomization analysis suggests that obesity and abdominal obesity are causally related to elevated circulating glutamate levels. Glutamate levels are not causally related to adiposity. Whether the downregulation of branched-chain amino acid catabolism in adipose tissue reported in obesity underlies this association should be explored.